Variation in yellow pigment content in bread (Triticum aestivum) and durum (Triticum turgidum var durum) wheat and synthetic hexaploids: genetic and environmental effects - RAM, SEWA; PATHANIA, MINAKSHI; TYAGI, BHUDEVA S (The Indian Journal of Agricultural Sciences, 2026)
Four hundred and ten genotypes representing Indian wheat varieties, selected germplasm lines, synthetic hexaploids and durum wheats were used in the present investigation to explore variability in yellow pigment content (YPC) in both bread (Triticum aestivum L.) and durum (Triticum turgidum Lvar durum) wheats. Microlevel test utilizing 0.2 g of the flour was developed to measure YPC in this investigation. There was strong correlation (R2=0.97) between values of YPC measured using microlevel test and AACC method. The data demonstrated large variation in YPC varying from 3.58 to 11.06 ppm with the average value of 7.08 ppm in durum wheats and 0.87 to 5.30 ppm with the average value of 3.19 ppm in bread wheat. Among bread wheat varieties, 1B/1R translocation lines showed statistically significant higher YPC as compared to non 1B/1R translocation lines (P